2020
DOI: 10.1016/j.neo.2019.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Targeting histone deacetylase SIRT1 selectively eradicates EGFR TKI-resistant cancer stem cells via regulation of mitochondrial oxidative phosphorylation in lung adenocarcinoma

Abstract: Lung adenocarcinoma (LAD) is a human malignancy successfully treated with the tyrosine kinase inhibitor (TKI) gefitinib; however, the enrichment of therapy resistant cancer stem cells (CSCs) in such patients is assumed to be a source of treatment failure. Evaluation of LAD cell populations treated with the TKI inhibitor gefitinib identified unique aspects of a subpopulation of tumor cells exhibiting stem-like properties and mitochondria-specific metabolic features along with their reliance on sirtuin 1 (SIRT1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…Consequently, administration of a SIRT1 inhibitor tenovin6 (TV6) in combination with gefitinib showed tumor regression in resistant xenograft models. Additionally, co-administration of TV6 leads to decrease in the dose of gefitinib necessary to induce tumor response in preclinical models ( Sun et al, 2020 ). A phase I/II trial enrolled 132 patients with advanced EGFR mutant NSCLC and randomized them to erlotinib plus entinostat or erlotinib plus placebo ( Witta et al, 2012 ).…”
Section: Clinical Utility Of Hdaci In Nsclcmentioning
confidence: 99%
“…Consequently, administration of a SIRT1 inhibitor tenovin6 (TV6) in combination with gefitinib showed tumor regression in resistant xenograft models. Additionally, co-administration of TV6 leads to decrease in the dose of gefitinib necessary to induce tumor response in preclinical models ( Sun et al, 2020 ). A phase I/II trial enrolled 132 patients with advanced EGFR mutant NSCLC and randomized them to erlotinib plus entinostat or erlotinib plus placebo ( Witta et al, 2012 ).…”
Section: Clinical Utility Of Hdaci In Nsclcmentioning
confidence: 99%
“…CSCs have the characteristics of carcinogenicity, multiple differentiation and self-renewal. Some scholars believe that tumor recurrence, metastasis and resistance to radiotherapy and chemotherapy were due to the existence of tumor stem cells [10]. The rst solid tumor to prove the existence of CSCs was BC; Al-Hajj et al proved that CD44 + /CD24 − /(low)-lineage cells isolated from BC tissue can form tumors in immunode cient mice [25].…”
Section: Discussionmentioning
confidence: 99%
“…T315I is the most frequent mutation causing imatinib resistance in patients with advanced CML or Ph + acute lymphocytic leukemia ( 43 ). It has been demonstrated that targeting Sphk1 and SIRT1 individually enhanced the sensitivity to TKI in various cancer cells, including acute myeloid leukemia, CML, renal cancer and lung adenocarcinoma ( 25 , 27 , 44 , 45 ), indicated its potential as a novel agent for the treatment of TKI-resistant leukemia. The present study lacked data on the treatment for leukemia cells with TKI in combination with SKI-II and EX527.…”
Section: Discussionmentioning
confidence: 99%